Cenosphere-Based 177Lu-Aluminosilicate Microspheres as a Theranostic β-Emitter for Selective Internal Radiation Therapy of Hepatic Tumors - Tatiana A. Vereshchagina; Ekaterina A. Kutikhina; Ivan A. Ushakov; Valery V. Zukau; Evgeniy A. Nesterov; Alexander G. Anshits (Science and Technology of Nuclear Installations)
The narrow fraction of the cenospheres of coal fly ash (30−50 μm; glass phase ∼ 90 wt. %) was used for the preparation of β-emitting 177Lu-bearing aluminosilicate microspheres. Two methods of chemical modification to encapsulate 177Lu3+ in the cenosphere’s aluminosilicate matrix were used, such as the formation of (i) microporous or (ii) meso/macroporous structure in the cenosphere shell followed by 175+176Lu3+ sorption. Conversion of Lu-loaded microspheres into poorly soluble forms was performed via the thermal treatment at 900–1200°C and then 176Lu was transformed to 177Lu by neutron activation procedure in a nuclear reactor. The 176Lu-bearing products were studied by PXRD, SEM, and EDX spectroscopy methods. It was established that the acid treatment of cenospheres resulting in a meso/macroporous structure in the cenosphere shell is the optimal nondestructive method to produce a microsphere precursor for Lu incorporation. The neutron activation of 176Lu-bearing microspheres resulted in 177Lu-microspheres that provide the specific radioactivity of 4.5 GBq/100 mg. The Lu leaching rate from 177Lu-microspheres in a blood simulator determined according to the State Standard (GOST) R 52126-2003 was about 10−6−10−7 g/cm2⋅day.